Peningkatan Aktivitas dan Hasil Belajar Sosiologi Siswa melalui Penerapan Model Pembelajaran Gagnon and Collay di Kelas XI IPS 6 Semeser II SMAN 5 Kota Jambi - Sutrisna, Sutrisna (Lentera: Jurnal Ilmiah Kependidikan, 2020)
This action research is motivated by the problem of the lack of student activity in sociology studies especially the integration and reintegration material as an effort to solve conflicts and integration problems, causing the low learning outcomes of students in sociology in class XI IPS 6 SMA Negeri 5 Jambi City. The contributing factor is that the teacher has been using lecture methods a lot, and the lack of use of learning models has caused students to not be active in learning, student activity in asking questions. % of 40 students. Most students show a passive attitude lacking enthusiasm, daydreaming, less attention, speaking when the teacher is explaining the material and showing attitudes that are not relevant to the learning situation Student learning outcomes are low. This study aims to find out how the action is carried out and the outcome process. Student activities are categorized in cycle I, cycle II is good, cycle III is very good. cycle I the average value of 64.50 cycle II increased 74.75 cycle III increased 88.25. An increase in students who completed 16 people in cycle I completed 25 people in cycle II increased 39 people in cycle III. Mastery class has increased cycle I by 40% cycle II 62.50% cycle III increased 97.50%. It can be concluded that an increase in the activities and learning outcomes of the sociology of the concept of social integration and reintegration through the application of the Gagnon and Collay Learning model. students in class XI IPS 6 Semester II SMAN 5 Jambi.